Upper and Lower Weakly $s$-$(τ_1,τ_2)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This article presents new classes of multifunctions called upper weakly $s$-$(τ_1,τ_2)$-continuousmultifunctions and lower weakly $s$-$(τ_1,τ_2)$-continuous multifunctions. Furthermore, several characterizations of upper weakly $s$-$(τ_1,τ_2)$-continuous multifunctions and lower weakly $s$-$(τ_1,τ_2)$-continuous multifunctions are discussed.
Keywords: $τ_1τ_2$-open set; upper weakly $s$-$(τ_1,τ_2)$-continuous multifunction; lower weakly $s$-$(τ_1,τ_2)$-continuous multifunction